Effectiveness of Skills Training in Increasing Women's Entrepreneurial Interest through Entrepreneurial Self-Motivation - Mustari, Mustari; Sirajjuddin, Andi Muchlis; Arisah, Nur (International Journal of Education, Vocational and Social Science, 2024)
The purpose of this study is to demonstrate how short training in skills like cosmetology may considerably help women launch their own enterprises. According to recent data from the Indonesian Businesswomen's Association (IWAPI), women significantly boost the economy of the nation through their entrepreneurial endeavors. The results of this study are anticipated to offer light on the likelihood that skill development might spark enthusiasm in establishing a business. Path analysis using SPSS was used to assess the direct impact of skill development on entrepreneurial interest as well as the indirect impact of skill development on entrepreneurial interest through entrepreneurial self-motivation. The results show that the direct impact of skill development is more closely connected with entrepreneurial self-motivation than the indirect impact of skill development on entrepreneurial interest. The findings demonstrated that both entrepreneurial self-motivation and concurrent skills training on entrepreneurial interest did not substantially affect the skills training variable. In reality, developing makeup skills takes just a short time while maintaining regular routines.